Model Pembelajaran Lompat Tinggi Gaya Flop Pada Siswa Sekolah Menengah Pertama - Sabila Nur Masturah (Almarhalah | Jurnal Pendidikan Islam, 2019)
The aim of this research and development is to produce the Flop Style High Jump learning model for junior high school students. This research uses research development (R D) research methods from Borg and Gall. The subjects in this research and development are Jakarta Junior High School students, which consist of 20 limited testing students (small group trials), 40 main trial athletes (field testing) and 50 Test effectiveness models.The stages in this study were: (1) needs analysis, (2) model development planning, (3) expert judgement, (4) limited testing (small group trials), (5) main trials (large group / field trials), (6) effectiveness testing. Effectiveness testing using the High Jump Style Flop motion assessment test to determine the level of high jump ability in the flop style of junior high school students, before and after the treatment of the flop style high jump learning model. From the preliminary tests performed, the average flop style jump learning average was 42.47, then after being given treatment in the form of a flop style high jump learning model, the flop style high jump level was 83.75. Then the flop style high jump learning model is effective in improving flop style high jump learning for junior high school students.Based on the results of the development, from the results of field trials and discussion of research results it can be concluded that: 1) With this flop style high jump learning model, students can learn and carry out learning effectively and efficiently. 2) With the flop style high jump learning model material that researchers have developed, students can understand theory material and high jump practice quickly and correctly.